Pengembangan Lembar Kerja Siswa (LKS) Berbasis STEM (Science, Technology, Engineering, and Mathematics) untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa SMP (UPEJ Unnes Physics Education Journal, 2020)
This research aims to develop STEM student worksheets to determine the characteristics and feasibility of the worksheets, and to know the increase of students creative thinking skills in secondary student. This research method uses the Research and Development (R & D) method. The subjects of the small group trial were IX A and the large scale test subjects were VIII A as the experimental class and VIII B as the control class. LKS is compiled by collaborating on the content of science, technology, engineering, and mathematics. The results of the feasibility test in terms of the feasibility of content, presentation, and language in criteria very feasible to use in learning activities. Readability test results indicates that LKS is easy to understand by students. The results of the n-gain test for the pretest-posttest score has high criteria. Based on large group trials, STEM-based student worksheets can improve creative thinking skills, namely on aspects of fluency, flexibility, elaboration, and originality that are characterized by an increase in the value of the pretest-posttest